WUJUD KETIDAKADILAN GENDER DALAM NOVEL POPULER INDONESIA: PERSPEKTIF FEMINISME - Hanim Widayati (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
The aim of this research was identify gender injustice in Indonesia’s popular novel. The research data based on the novel had title Bibir Merah by Achmad Munifwas published by Navila on August 2004 and Curahan Hati Sang SPG by Wenda Koiman was publised by Story house in 2013. Getting data by Read, View, and Record technique (BSC). Study result stated that (1) gender injustice based on indonesia’s populer novel such as first negative labeling/ stereotypes: woman as a materialistic, whore easily and a playful object for man. Second, abuse: sexual abuse purpose for position as sexual abuse victim and working risk. Psychological abuse respond was common condition, weak, incapable for doing and internal conflict happen. Third, double burden.